(untitled) (Revista Argentina de Cirugía, 2022)
Introduction: The placement of Central Venous Catheters (CVC) is a frequent procedure due to the increase in serious patients or who require intravenous therapy for a long time. Be used under certain criteria, infection rules, valuing the benefit in each case; it is not free of complications, risks and adverse events. A Checklist for the Safety of Patients with Central Venous Catheter was implemented, with the intention of improving the quality of care, provide patient safety, and reduce morbidity and mortality, hospital stay, and health costs. Material and methods: 136 records lists for verification of patient with central venous catheter (CVC), implemented in the service of General Surgery of the Central Air Force Hospital, were analyzed between january 2012 - january 2013. An analysis of the place of preparation and equipment necessary for the procedure; discussed data in four stages: before, during and after the procedure. and follow-up of the patient post of catheter. Analyzed the failures detected in the data record of filiation, of the material needed for the procedure and each stage; and finally analyzed records of the removal of the catheter. Results: 136 procedures were performed by medical residents in General Surgery; 125 (91.91%) in the operating room, 6 (4.42%) in the general room, 4 (2.94%) in UTI, and 1 (0.73%) in UCO; 121 (88.97%) emergency and 15 (11.03%) in elective way; 76 (55.88%) for PVC and hemodynamic management measurement; 27 (19.86%) for antibiotic therapy iv; 15 (11.03%)...